Corrosion behaviour, microstructure and phase transitions of Zn-based alloys - Yildiz, AK; Kaplan, M (Indian Academy Sciences, 2004)
This paper is aimed at investigating the corrosion behaviour, microstructure and phase transitions of Zn-based alloys with different compositions. The corrosion tests are carried out both in acidic medium using 1 N HCl solution and in temperature dependence of thermogravimetric analysis (TGA). In the two different media, in particular, the corrosion behaviour of Zn-based alloys with respect to Al and Si contents is examined, and microstructure in acidic and TGA and phase transformations in TGA are also studied. Corrosion mechanism in TGA is also examined in terms of oxidation parameters and activation energies. The study reveals that corrosion behaviour of Zn-based alloys in acidic medium shows sometimes an increase and sometimes a decrease with time due to Al content which assists in delaying the corrosion by forming a oxide layer on the surface of Zn-based alloys. This property does not appear in temperature dependence of TGA. Further, Si content appears to remain in main matrix without being affected by acidic solution. On the other hand, it is observed that in microstructure, AlO(Al2O3), ZnO oxides and Zn-Cu phase precipitations are formed in main matrix, grain boundaries and partially inside the grains.
Keywords: Zinc-based alloys; weight loss; acidic corrosion; thermogravimetric analysis